Evaluation of SIAKAD ITSK RS dr. Soepraoen using Technology Acceptance Model (TAM) - Ahsanun Naseh Khudori; Risqy Siwi Pradini; Nindynar Rikatsih (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Institut Teknologi, Sains, dan Kesehatan (ITSK) RS dr. Soepraoen is one of the higher education institutions that implements academic information systems in the process of providing education. The academic information system (SIAKAD) involves many users and many data processings, so there is possibility of problems with network access. Therefore, an evaluation is needed to determine user’s acceptances of the performance of SIAKAD which has been used so far at ITSK. The evaluation model proposed in this research is the Technology Acceptance Model (TAM), which is a model that provides perceptions based on the experiences experienced by users. This research used a questionnaire instrument which was distributed to all SIAKAD ITSK users. The expected result is a positive percentage that will describe the correct system performance and a negative percentage that can be an input for further improvements to SIAKAD ITSK.